2021
DOI: 10.22605/rrh6639
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy prevention in rural Indonesia: a participatory action research

Abstract: Introduction: Adolescent pregnancy remains a difficult problem in developing countries, including Indonesia. Pregnancy at an early age is a risk factor for maternal and infant mortality. A recent report indicates that adolescent pregnancy is even higher in rural areas. Therefore, this study aims to identify factors associated with adolescent pregnancy in rural Indonesia and formulate intervention actions to reduce the teenage pregnancy rate. Methods: Participatory action research (PAR) was conducted in the rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…This result means that a young female had a 99.9% probability of not having tobacco use behavior. The current phenomenon might be caused by the Indonesian rural population's characteristics that still practice strict cultural practices [16]. In Indonesian culture, smoking for young and adult women is considered inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result means that a young female had a 99.9% probability of not having tobacco use behavior. The current phenomenon might be caused by the Indonesian rural population's characteristics that still practice strict cultural practices [16]. In Indonesian culture, smoking for young and adult women is considered inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies in Indonesia found that the prevalence of youth tobacco consumption is higher in rural areas [6], [13]. People living in rural areas of Indonesia experience significant disparities in health services and socio-economic opportunities compared to those living in urban settings [14], [15], [16]. These disparities have put people living in rural areas as a disadvantaged population.…”
Section: Introductionmentioning
confidence: 99%
“…The risks arise regarding lack of nutrition, blood issues, and disease-carrier mother [1,2]. In developing countries, pregnant women are faced with high-risk pregnancies [3][4][5] This is mainly caused by inadequate information about maternal health awareness of blood-related disease [6,7] Furthermore, due to minimum awareness, the risk spiked dramatically [6,8]. All of these issues lead to an increase in the foetal mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other factors related to teenage pregnancy are low family income, marital status, lack of communications, and parents' history of teenage pregnancy, low absorption of reproductive health services, juvenile delinquency, and social and cultural norms. 1,7,8 In teenage pregnancy, there is an increased health risk to the mother and the baby to be born. 9 There are many negative impacts of teenage pregnancy, including anemia risk, the necessity of the baby being treated in the NICU, and postpartum complications.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other factors related to teenage pregnancy are low family income, marital status, lack of communications, and parents’ history of teenage pregnancy, low absorption of reproductive health services, juvenile delinquency, and social and cultural norms. 1,7,8…”
Section: Introductionmentioning
confidence: 99%